Long-term Follow-up of Hemostatic Molecular Markers during Remission Induction Therapy with All-Trans Retinoic Acid for Acute Promyelocytic Leukemia - Watanabe, Reiko; Murata, Mitsuru; Takayama, Nobuyuki; Tokuhira, Michihide; Kizaki, Masahiro; Okamoto, Shinichiro; Kawai, Yohko; Watanabe, Kiyoaki; Murakami, Hiroshi; Kikuchi, Masao; Nakamura, Shin; Ikeda, Yasuo; For Keio Hematology-Oncology Cooperative Study Group (KHOCS) (Thrombosis and Haemostasis, 1997)
Hemostatic molecular markers were serially monitored in a prospective fashion during remission induction therapy with all-trans retinoic acid (ATRA) in sixteen patients with acute promyelocytic leukemia (APL). One patient with leukocytosis before treatment and three patients who later developed hyperleukocytosis also received chemotherapy with behenoyl Ara-C and daunorubicin. Plasma levels of E-fragment of fibrin and fibrinogen degradation product (FDP-E), FDP-D dimer (D-D), thrombin-antithrombin complex (TAT), and plasmin-α2 plasmin inhibitor complex (PIC) were markedly elevated in all but one patient before treatment, and these parameters decreased to normal or near normal ranges in most patients within the first 7 days of treatment. Interestingly, we have found that these parameters were again elevated during the later course of ATRA therapy (after day +7) in eleven patients for various reasons including cytotoxic chemotherapy (3 cases), fever (5 cases; 2 cases with apparent infection, 3 cases without known etiology), Caesarean section (1 case), and no apparent etiology (2 cases). Three patients showed bleeding complications during reelevation of molecular markers, but none developed thrombosis. Plasma elastase-α1 proteinase inhibitor complex (E-α1PI) was markedly elevated in all patients at diagnosis and did not decrease significantly during ATRA therapy. Plasma tissue factor antigen was mildly elevated in one out of four patients studied, and thrombomodulin was elevated in two out of ten patients tested. These results confirmed the rapid normalization of coagulopathy during the early phase of remission induction therapy with ATRA but suggest that re-elevation of molecular markers occurs frequently during the later course of ATRA therapy.